Introduction to financial accounting : based on International Financial Reporting Standards - Annand, David; BC Open Textbook Project; BCcampus (Valley Educational Services Ltd., 2016)
"Based on International Financial Reporting Standards, this textbook was written by David Annand, EdD, MBA, CPA, CA, Professor of Accounting in the Faculty of Business at Athabasca University. Each chapter includes questions and comprehension problems for self-study. Solutions are provided. Additional end-of-chapter assignment problems are also included. The text and ancillary materials are freely-sharable under a Creative Commons CC-BY-SA-NC licence. The .pdf version of the text is extensively bookmarked for easy access and onscreen reading. Suggested solutions are linked to the appropriate material in this version. Separate .docx and .pdf versions of the text and student solutions manual are available. All files are available in both .pdf and .docx formats. The workbook provides formatted outlines to all problems contained in the text and exam bank. Students can print outlines as they need them, and fill in responses manually"--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Title from PDF; description based on version 2.2 viewed on April 6, 2017; last updated February 22, 2017.
Keywords: Accounting -- Textbooks; Electronic books